Prematurity and parental self-efficacy: The Preterm Parenting & Self-Efficacy Checklist - Pennell, C.; Whittingham, K.; Boyd, Roslyn; Sanders, M.; Colditz, P. (2012)
There is a lack of research investigating parental self-efficacy in parents of infants born preterm as well as a paucity of parental self-efficacy measures that are domain-specific and theoretically grounded. This study aimed to compare parental self-efficacy in parents of infants born term, preterm and very preterm as well as to test whether parental self-efficacy mediates the relationship between psychological symptoms and parental competence. In order to achieve this, a new measure of parental self-efficacy and parental competence relevant for the preterm population and consistent with Bandura's (1977, 1986, 1989) conceptualisation of self-efficacy was developed. Participants included 155 parents, 83 of whom were parents of very preterm (GA < 32 weeks), 40 parents of preterm (GA < 37 weeks) and 32 parents of term born infants. Parents completed the Preterm Parenting & Self-Efficacy Checklist (the new measure), Family Demographic Questionnaire, Depression Anxiety Stress Scale and Self-Efficacy Questionnaire. This initial study indicates that the Preterm Parenting & Self-Efficacy Checklist has adequate content validity, construct validity, internal consistency and split half reliability. Contrary to expectations, parents of very preterm infants did not report significantly lower overall levels of parental self-efficacy or significantly higher levels of psychological symptoms compared to parents of preterm and term infants. Parental self-efficacy about parenting tasks mediated the relationship between psychological symptoms and self perceived parental competence as predicted. Clinical implications of the results and suggestions for future research are discussed. © 2012.